2020
DOI: 10.1002/cssc.202001428
|View full text |Cite
|
Sign up to set email alerts
|

Potential‐ and Buffer‐Dependent Catalyst Decomposition during Nickel‐Based Water Oxidation Catalysis

Abstract: The production of hydrogen by water electrolysis benefits from the development of water oxidation catalysts. This development process can be aided by the postulation of design rules for catalytic systems. The analysis of the reactivity of molecular complexes can be complicated by their decomposition under catalytic conditions into nanoparticles that may also be active. Such a misinterpretation can lead to incorrect design rules. In this study, the nickel‐based water oxidation catalyst [NiII(meso‐L)](ClO4)2, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 92 publications
0
16
0
Order By: Relevance
“…Substitution of the buffer with bicarbonate demonstrated a decrease in redox potential for both the Ni IV /Ni III couple and for electrocatalytic water oxidation process, indicating that bicarbonate acts as a non‐innocent axial ligand, oxidized during the redox process. Furthermore, we recently found this catalyst goes through a pH and buffer dependent decomposition pathway: a layer of NiO x was formed in a pH 7 phosphate buffer verified by in situ characterization of electrochemical quartz crystal microbalance measurements, while no indication of NiO x layer formation at a pH of 6.5 in phosphate buffer nor in a pH 7.0 acetate buffer, albeit exhibiting low activity [32] . A similar Ni catalyst with complete N ‐methylation ([Ni(TMC)(CH 3 CN)](NO 3 ) 2 TMC=1,4,8,11‐tetramethyl‐1,4,8,11‐tetraazacyclotetradecane, Ni‐4 , Figure 14) was subsequently synthesized by Li et al [73] .…”
Section: Homogeneous Nickel‐based Wocsmentioning
confidence: 90%
See 2 more Smart Citations
“…Substitution of the buffer with bicarbonate demonstrated a decrease in redox potential for both the Ni IV /Ni III couple and for electrocatalytic water oxidation process, indicating that bicarbonate acts as a non‐innocent axial ligand, oxidized during the redox process. Furthermore, we recently found this catalyst goes through a pH and buffer dependent decomposition pathway: a layer of NiO x was formed in a pH 7 phosphate buffer verified by in situ characterization of electrochemical quartz crystal microbalance measurements, while no indication of NiO x layer formation at a pH of 6.5 in phosphate buffer nor in a pH 7.0 acetate buffer, albeit exhibiting low activity [32] . A similar Ni catalyst with complete N ‐methylation ([Ni(TMC)(CH 3 CN)](NO 3 ) 2 TMC=1,4,8,11‐tetramethyl‐1,4,8,11‐tetraazacyclotetradecane, Ni‐4 , Figure 14) was subsequently synthesized by Li et al [73] .…”
Section: Homogeneous Nickel‐based Wocsmentioning
confidence: 90%
“…Recently, the formation of NiO x was confirmed with a homogeneous macrocyclic nickel(II) complex [Ni(meso-L)](ClO 4 ) 2 (L = 5,5,7,12,12,14-hexamethyl-1,4,8,11-tetraazacyclotetradecane) as catalyst by our group. [32] The structure was originally reported as a homogeneous WOC at pH 7, due to instability of the NiO x formed during bulk electrolysis. The NiO x desorbed rapidly upon removal of applied bias, thus the metal-based nanoparticle species eluded detection.…”
Section: Distinguishing Between Homogeneous and Heterogeneous Catalystsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the alkaline medium, a complete conversion of the molecular Ni complexes to the active catalyst Ni(OH) 2 /Ni(O)OH has been reported earlier whereas a partial conversion has also been detected for some of the complexes. [62][63][64] Looking at the previous results, we can consider three different active catalysts: (i) the molecular complex, (ii) the interface of the molecular complex and Ni(OH) 2 /Ni(O)OH, and (iii) Ni(OH) 2 /Ni(O) OH.…”
Section: Electrocatalytic Oxygen Evolution Reaction (Oer) Studiesmentioning
confidence: 99%
“…25 This layer desorbs from the electrode at fewer anodic potentials and prevents ex situ detection. 25 The group also showed that catalyst decomposition is a buffer-dependent reaction. 25 It was recently demonstrated that during OER and at very low overpotentials, a tetranuclear Ni complex is decomposed to Ni (hydr)oxide.…”
Section: ■ Introductionmentioning
confidence: 99%